Context dependency of the density–body mass relationship in litter invertebrates along an elevational gradient. (September 2015) - Xu, Guorui; Zhang, Shuang; Lin, Yinghua; Ma, Keming
Abstract: How community structure responds to environmental changes in space and time is a key concern in ecology. As a synthesized indicator of community structure, the density–body mass (DBM) relationship reflecting body size distributions can serve as a linkage between community response and ecological processes and function. However, the drivers of the spatial and temporal shifts in the DBM relationship for brown food webs remain largely unknown. This study aimed to find the elevational pattern of body size distributions of litter invertebrate communities and understand the causes of climate and resource factors shaping this pattern in different spatio-temporal contexts. We identified the elevational pattern of body size distributions of litter invertebrates in a temperate montane forest and, for the first time, examined this pattern by taking account of the temporal contexts integrating the growing and dormant seasons. Furthermore, we assessed the relative roles of climate factors (i.e., temperature, light, and moisture) and resource factors (i.e., litter quality and quantity) in body size distribution patterns. In general, we demonstrated litter invertebrate communities were size-structured at all elevations and in different seasons, which underpins the DBM. However, the elevational patterns of the DBM slopes varied between seasons: In the growing season the DBM slopes were shallower with increasing elevation. Contrasting, the DBM slopes were steeper with increasing elevation in the dormant season. This is indicating that along the elevation, the larger litter invertebrates benefited more in the growing season compared with the smaller invertebrates, which benefited more in the dormant season. The drivers of the DBM relationship were context dependent: (1) temperature was a fundamental driver for the DBM relationship across space and time, with increasing temperature benefiting smaller invertebrates; (2) crown density only matters in the dormant season, with increasing light intensity benefiting larger invertebrates. No impact of soil moisture on the body size distributions was detected; and (3) litter availability impact varied with season in quality (i.e., litter C:N and C:S ratios) and quantity (i.e., litter amount), mainly functioning in the growing and the dormant season, respectively. This finding would enhance a more predictive understanding of how environmental change may restructure ecosystems and soil functioning from an allometric scaling perspective in the context of global warming. Highlights: Contrasting elevational patterns of the DBM slopes existed in different seasons. Increasing temperature benefited smaller litter invertebrates in both seasons. Litter C:N and C:S ratios were related with DBM slopes in the growing season. Litter amount and richness were related with DBM slopes in the dormant season.